Desenvolvimento de linhagens anãs para a obtenção de híbridos de tomate do tipo Santa Cruz - Gomes, Danilo Araújo (2021)
Increasing the productivity of tomato hybrids is a constant search among breeders, for which a viable alternative is to reduce the size of the plants, allowing a greater number of plants per area and a greater number of clumps per linear meter of stem. Changing the plant's morphology by using a dwarf line to obtain hybrids may be an excellent alternative to achieve these objectives, a strategy that has already been used in the mini-tomato segment. However, the exploitation of this technology and its benefits for the Santa Cruz segment is not yet a reality. Therefore, the general objective of this work was to select BC1F2 and BC1F3 populations of dwarf tomato type Santa Cruz round with agronomic potential, fruit quality and resistance to pests. This research was carry out in two stages: first, the performance of dwarf populations obtained after a backcross (BC1F2) and, then, the performance of dwarf populations obtained after a self-fertilization (BC1F3) of plants from populations selected in BC1F2. Both trials were carried out at the vegetable trial station at the Federal University of Uberlandia – Monte Carmelo Campus, MG, Brazil. For the first experiment, was used a randomized block design with 15 treatments and 4 replications. The genetic material evaluated consisted of 11 dwarf tomato BC1F2 populations, plus both parents (recurrent and donor) and two commercial hybrids. In this first stage we conclude, the mean fruit weight, transverse diameter, and pulp thickness of the dwarf populations increased significantly after the first backcross, and most of them exhibited fruit shape similar to that of the Santa Cruz segment. The dwarf BC1F2 populations UFU-Sci#11 and UFU-Sci#12 showed promise for obtaining lines and, subsequently, Santa Cruz type hybrids. For the second study, the aim of was to estimate genetic divergence and select BC1F3 populations of dwarf tomato plant within the Santa Cruz segment by conventional techniques and computational intelligence. The genetic material evaluated consisted of 13 BC1F3 dwarf populations, originated from self fertilization of plants selected in dwarf populations BC1F2 plus both parents (recurrent and donor) and two commercial hybrids. Genetic dissimilarity in relation to the donor parent could be confirmed through both methodologies. However, computational intelligence using Kohonen self-organizing maps (SOM) was able to detect differences and organize the similarities among the populations in a more consistent manner, resulting in a larger number of groups. Among the BC1F3 populations, UFU-SC#3 and UFU-SC#5 stood out for agronomic traits, and UFU-SC#10 and UFU-SC#11 stood out for quality parameters. It is suggested for the next stage to perform the second backcrossing to obtain genotypes and, later, tomato dwarf lines with Santa Cruz fruits, which allowed the obtaining of hybrids from dwarf lines with reduced internodes length.